2015
DOI: 10.1002/pbc.25700
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement Follow‐Up After the Death of a Child as a Standard of Care in Pediatric Oncology

Abstract: After a child’s death to cancer, families commonly want continued connection with the healthcare team that cared for their child, yet bereavement follow-up is often sporadic. A comprehensive literature search found that many bereaved parents experience poor psychological outcomes during bereavement and that parents want follow-up and benefit from continued connection with their child’s health care providers. Evidence suggests that the standard of care should consist of at least one meaningful contact between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 110 publications
1
113
0
1
Order By: Relevance
“…The strongest evidence (e.g., high quality) was found for four standards: Psychosocial assessment during cancer treatment and in survivorship; neurocognitive monitoring for children at risk; psychosocial support; and interventions for painful procedures . Although based on a less rigorous literature, moderate evidence was found for assessment of financial issues; addressing behavioral health issues of parents; psychoeducation; social interaction; supportive services for siblings; assessment and monitoring of adherence; early integration of palliative care; and bereavement . Mixed moderate and high quality of evidence was found for survivorship .…”
Section: Resultsmentioning
confidence: 99%
“…The strongest evidence (e.g., high quality) was found for four standards: Psychosocial assessment during cancer treatment and in survivorship; neurocognitive monitoring for children at risk; psychosocial support; and interventions for painful procedures . Although based on a less rigorous literature, moderate evidence was found for assessment of financial issues; addressing behavioral health issues of parents; psychoeducation; social interaction; supportive services for siblings; assessment and monitoring of adherence; early integration of palliative care; and bereavement . Mixed moderate and high quality of evidence was found for survivorship .…”
Section: Resultsmentioning
confidence: 99%
“…These concerns may diminish with time, but bereaved siblings have also reported that long‐term outcomes (e.g., educational and career goals) may be affected by the loss . This highlights the need to provide ongoing support to families, especially after a child has died …”
Section: Resultsmentioning
confidence: 99%
“…Young patients have the right to be fully informed about their illness and treatment and desire empathetic, direct communication with physicians . Adolescents with cancer report the importance of being well‐informed and included in decision‐making about their treatment and end of life care . Tailoring of the message and choice of the voice are important because not all want full details of their condition, care, and prognosis and preferences vary for preferred source.…”
Section: Resultsmentioning
confidence: 99%